Analisis Yuridis Terhadap Pencoretan Pihak dalam Akta Notaris yang Berindikasi Nominee Serta Menimbulkan Ketidakpastian Hukum (Studi Penelitian di Majelis Pengawas Daerah Kota Batam) - Elviani, Elviani; Respationo, Soerya; Tartib, Muhammad; Erniyanti, Erniyanti (Universitas Ekasakti, 2023)
This research uses normative research methods supported by empirical research. By examining the positive laws that apply in Indonesia and analyzing data obtained directly from the field or facts that occur in society. The aim is to find out how the legal regulations, the implementation of deletion and the factors that become obstacles/obstacles and solutions to the deletion of parties in Notarial deeds which are indicated as nominees occur in Indonesia. The research results show that legal regulations in Indonesia still do not have specific regulations regarding the removal of parties in Notarial Deeds who are indicated as nominees. However, in practice, deletions in a Notarial Deed can refer to Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notaries. Researchers hope that there will be special rules regarding the procedure for writing off a Notarial Deed, based on Court Decision regulations. So as not to create legal uncertainty in implementing law in Indonesia.